Talus bipartitus etiology - is neonatal infection involved - Boszczyk, A. M; Kołodziej, Ł (Acta chirurgiae orthopaedicae et traumatologiae Čechoslovaca, 2016)
UNLABELLED: Talus bipartitus is a rare skeletal variation. Several causative factors have been proposed, but none of them seem to be convincing. We hypothesize that talus bipartitus may result from ossification disruption in neonatal period caused possibly by an infection. The observations supporting this link are discussed. The hypothesis is supported by two cases with symptomatic talus bipartitus illustrating the postulated connection. KEY WORDS: ankle, pain etiology, talus abnormalities, talus bipartitus.
Keywords: Talus; dospělí; Pain; bolest; Ankle Joint; lidé; talus; Female; mužské pohlaví; Male; Adult; ženské pohlaví; hlezenní kloub; Humans